2013
DOI: 10.1016/j.ecolind.2013.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Responses of foraminiferal assemblages to ENSO climate patterns on bank reefs of northern Bahia, Brazil: A 17-year record

Abstract: false2016-03-16T23:02:09

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 39 publications
(62 reference statements)
1
18
0
Order By: Relevance
“…We found that sponges appeared unaffected by the increase in seawater temperature and actually increased in abundance after the ENSO event. This is in stark contrast to all other benthic organisms in this study area that experienced mass mortalities, including Foraminifera, corals, echinoderms, bryozoans and ascidians [54], [41], [42], [43], [44], [45]. Our result suggest that tropical sponges in this region may have increased resilience to higher sea surface temperatures compared to other organisms, and this has potentially important implications for reef systems elsewhere.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…We found that sponges appeared unaffected by the increase in seawater temperature and actually increased in abundance after the ENSO event. This is in stark contrast to all other benthic organisms in this study area that experienced mass mortalities, including Foraminifera, corals, echinoderms, bryozoans and ascidians [54], [41], [42], [43], [44], [45]. Our result suggest that tropical sponges in this region may have increased resilience to higher sea surface temperatures compared to other organisms, and this has potentially important implications for reef systems elsewhere.…”
Section: Discussionmentioning
confidence: 60%
“…Annual average salinity varies little (35–36), although within reef-top shallow pools, salinity can range from 35 to 39 (see [52]). The pH of seawater varies only between 8.1 and 8.2, with no clear seasonal patterns (see [54], [55]). The coast is influenced by winds arising from the NE and E during the spring-summer, and winds coming from the SE and E during the autumn-winter season.…”
Section: Methodsmentioning
confidence: 99%
“…Low diversity, low density photosymbiotic assemblages are not atypical of marginal reefs and reefs influenced by ENSO climatic patterns (Kelmo and Hallock, 2013). Our…”
mentioning
confidence: 79%
“…Therefore, according to Clausen and Roth [84], many species are able to acclimate physiologically to increased temperatures, a suggestion validated by recent studies [85], [86] as well as by the response displayed by F. gravida and S. stellata , which seemed quite resistant to the elevated temperatures recorded in northern Bahia during the ENSO period. However, even endemic species ( M.hispida and M.harttii ) or widely distributed [87], disease resistant [88] corals, such as P.astreoides , succumbed to excessive and prolonged periods of warming, such as the strong 1997–8 ENSO followed by the 1999–2000 strong La Niña-related conditions of increased rainfall and therefore increased runoff of terrestrial nutrients [34]. No significant step change in the studied community was noticed between 2001–2005 when thermal anomalies varying from 0.25°C to 0.75°C were reported for the coast of Bahia [26], nor during the 2009–10 ENSO that caused bleaching in another regions [89].…”
Section: Discussionmentioning
confidence: 99%
“…Annual average salinity varies little (35–36), although within reef-top shallow pools, salinity can range from 35 to 39. The pH of seawater varies only between 8.1 and 8.2, with no clear seasonal patterns (see [34]). The coast is influenced by winds arising from the NE and E during the spring-summer, and winds coming from the SE and E during the autumn-winter season.…”
Section: Methodsmentioning
confidence: 99%